Commonness, rarity, and intraspecific variation in traits and performance in tropical tree seedlings. (28th September 2015) - Umaña, María Natalia; Zhang, Caicai; Cao, Min; Lin, Luxiang; Swenson, Nathan G.
Abstract: One of the few rules in ecology is that communities are composed of many rare and few common species. Trait‐based investigations of abundance distributions have generally focused on species‐mean trait values with mixed success. Here, using large tropical tree seedling datasets in China and Puerto Rico, we take an alternative approach that considers the magnitude of intraspecific variation in traits and growth as it relates to species abundance. We find that common species are less variable in their traits and growth. Common species also occupy core positions within community trait space indicating that they are finely tuned for the available conditions. Rare species are functionally peripheral and are likely transients struggling for success in the given environment. The work highlights the importance of considering intraspecific variation in trait‐based ecology and demonstrates asymmetry in the magnitude of intraspecific variation among species is critical for understanding of how traits are related to abundance.